Ação do laser de baixa intensidade no processo de reparo ósseo de ratos - Buchignani, Vivian Chiacchio (2015)
The objective of this study was to evaluate the bone repair process in the tibia of rats to low-power laser therapy (LLLT), by histomorphometric analysis. For this we used 20 adult albino rats (Rattus norvegius albinus, Wistar), which were divided in to two groups according to treatment: Control Group (CG) - animals submitted to the creation of the bone defect in the left tibia without application of LLLT; and Experimental Group (GL) - animals submitted to the creation of the bone defect in the right tibia and a single session of LLLT. Bone defects in the tibia 2mm animals from all groups were prepared. In the immediate postoperative period was applied to the right tibia of animals the GL group, LLLT at a total dose of 32 J / cm2com power of 0.03 W at 133/2 per point. After periods of 14 and 28 days after the application of the laser, the animals were sacrificed for removal of specimens. After obtaining the specimens followed by histological processing for paraffin embedding and later histomorphometric analysis. The GL group had higher bone formation compared to the control group. Based on the results of this study, it can be concluded that the use of LLLT was able to accelerate the bone healing process and increase the area of newly formed bone tissue, with only one application of LASER in the immediate postoperative period